Pengaruh Pertumbuhan Aktiva Dan Ukuran Perusahaan Terhadap Struktur Modal Pada Perusahaan Perbankan - Rr. Suprantiningrum (Media Ekonomi dan Manajemen, 2011)
Abstract Financing or capital structure decision is one of the important decisions in the continuity of operations. Fund companies can be sourced from within and outside the company. And in these capital structure decisions must consider the factors that influence in order to obtain optimal capital structure. This study aimed to investigate the influence and size of the Company Asset Growth of Capital Structure on the Banking Companies either partially or simultaneously. The data used are secondary data. The population in this research is publicly traded banking company in Indonesia Stock Exchange 2003-2007. Sampling technique used is purposive sampling and acquired 22 companies in the sample study.Analysis of the data used is the F-test, t-test, and Multiple Linear Regression. The Results of F-test that all independent variables affect the dependent variable with a significance level of 5%. While the results of ttest states that the variables of ownership structure and growth of assets does not affect the capital structure; Profitability has a negative and significant influence, while the size of the company's positive impact on the banking company's capital structure. Keywords: Capital Structure, Asset Growth, Company Size